2016
DOI: 10.14238/pi46.2.2006.82-6
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity in beta-HbE thalassemia patients

Abstract: Background Thalassemia is a monogenic disease, yet the clini-cal manifestations (phenotype) are variable although they havethe same genotype. The clear-cut correlation between genotypeand phenotype in β-thalassaemia/HbE patients remains unex-plained. There are several factors that play a role in the severity ofthe clinical manifestations, i.e. two alpha-gene deletion, homozy-gote Xmn1 polymorphism +/+, -+-++, ++-++ haplotype, and hemo-globin Constant Spring.Objective To understand the clinical diversity of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…HbA2 in beta0 thalassemia/hemoglobin E. In Indonesia, the most common beta-globin gene mutations are IVS1-nt5 (G C), IVS1-nt1 (G T), (AAC AGC ). Study from Semarang transfusion unit on a β thalassemic patient with routine transfusion the most common mutation is HbE/IVS1-nt5 (55.3%) followed by IVS1-nt5/IVS1-nt5 7,8 and HbE/Cd35 each as much as 13.2%.…”
Section: Introductionmentioning
confidence: 98%
“…HbA2 in beta0 thalassemia/hemoglobin E. In Indonesia, the most common beta-globin gene mutations are IVS1-nt5 (G C), IVS1-nt1 (G T), (AAC AGC ). Study from Semarang transfusion unit on a β thalassemic patient with routine transfusion the most common mutation is HbE/IVS1-nt5 (55.3%) followed by IVS1-nt5/IVS1-nt5 7,8 and HbE/Cd35 each as much as 13.2%.…”
Section: Introductionmentioning
confidence: 98%
“…41 The data from Indonesia reported that genotypes (-/-) and (+/) of the XmnI locus is not related with the absolute amount of HbF in HbE/ β thalassemia patients. 42 The same group reported that β thalaseemia mutation type is not a factor that influence clinical manifestation, apartfrom the IVSl-nt 5 (G>C) that is related to severe clinical features, co-inheritance of a globin deletion type 3,7 kb (co/o-) is related to mild clinical manifestation, while αglobin chain triplication did not exist both mild and severe groupsand therefore its relation with clinical manifestation could not be assessed. Study also showed that Xmnl heterozygote polymorphisms (polymorphism in-150°y globin gene, C>T) werefound both in the mild and severe groups, therefore this kind of polymorphism is not afactor that influences clinical manifestations.…”
Section: Quantitative Traits Locus (Qtl) Of Xmni Bcl11a and Hbs1l-mybmentioning
confidence: 99%
“…Therefore, carrier screening protocol and prenatal testing have to be designed on a regional basis (Wahidiyat et al. ).…”
Section: Genetic Diseases In Indonesiamentioning
confidence: 99%
“…This variation resulted to unequal anticipated carrier testing and prenatal testing workload. Therefore, carrier screening protocol and prenatal testing have to be designed on a regional basis (Wahidiyat et al 2006 (Ariani et al 2014).…”
Section: Genetic Diseases In Indonesiamentioning
confidence: 99%